Abdominal Pain, Conjunctival Icterus, and Melena in a Man With Recent Endocarditis - John W. Ostrominski; Mark J. Ferreira; Linda S. Lee (Annals of Internal Medicine: Clinical Cases)
Gastrointestinal bleeding is a common clinical entity associated with substantial morbidity and mortality. Upper gastrointestinal hemorrhage in particular requires swift recognition and management, and additionally engenders a broad differential diagnosis. Although rare, hemobilia, bleeding from or into the biliary tract, is an important diagnosis to consider at the bedside because of its unique risk factors, as well as diagnostic and therapeutic considerations. Here, we describe the clinical presentation of a man with hemobilia, highlighting key contemporary risk factors, diagnostic modalities, and therapeutic interventions.